M19. NIGROSTRIATAL CONNECTIVITY AND THE PREDICTION OF THOUGHT DISTURBANCE IN EARLY PSYCHOSIS. (18th May 2020) - Homan, Philipp; Malhotra, Anil; Lencz, Todd; De Rosse, Pamela
Abstract: Background: Dopamine neurons are known to fire both tonically and phasically, resulting in tonic dopamine concentrations and spikes in those concentrations (often referred to as transients). Empirical evidence has shown elevated activity in the striatum in response to neutral stimuli which correlated with positive symptoms, in line with the proposed increased prediction errors. The increase of sponataneous phasic dopamine release in early psychosis should also be evident by altered resting state connectivity between the midbrain and its dopaminergic projections to the dorsal striatum. Given that all antipsychotics bind to striatal dopamine D2 receptors, we assumed that this altered functional connectivity would also relate to treatment efficacy of those antipsychotic agents. Using striatal seeds, and extending our own group's prior work exploring striatal connectivity, we computed an index of nigrostriatal connectivity and estimated its relationship with improvement of positive symptoms under antipsychotic monotherapy. Methods: We conducted a parcellation of subcortical midbrain structures including the substantia nigra and ventral tegmental area in two independent early phase psychosis cohorts. Early phase psychosis was defined as having an antipsychotic life time exposure of less than 52 weeks. Patients were between 15 and 40 years old and with a DSM-V-defined diagnosis of schizophrenia, schizoaffective disorder, or bipolar disorder with psychotic features and provided informed consent to participate in the study. Exclusion criteria were active alcohol or substance abuse disorders, serious medical conditions, and pregnancy. Preprocessing involved the state-of-the art Human Connectome Project pipeline and extensive correction for motion artifacts. After parcellation, we extracted the connectivity values of the striatal seeds with the substantia nigra and calculated an improved version of the striatal connectivity index with the R-package sci developed by the presenter and freely available online at http://github.com/philipphoman/sci . Results: We found that nigrostriatal connectivity was predictive of treatment efficacy in a sample of 41 patients with early phase psychosis. Indeed, individual differences in this connectivity index explained 18% of the variance of positive symptom improvement under antipsychotic treatment. Importantly, we replicated this effect in an independent replication cohort of 40 early phase psychosis patients, where we found that the identical model explained 11% of the variance in symptom improvement. Discussion: There is an urgent need for diagnostic and prognostic biomarkers in psychotic disorders, and our results suggest that nigrostriatal connectivity is a promising candidate for a prognostic biomarker for antipsychotic treatment.